(a^2+b^2)xy+ab(x^2+y^2) = a^2xy+abx^2 +b^2xy+aby^2 =ax(ay+bx)+by(bx+ay) =(ax+by)(ay+bx)
(a^2+b^2)xy+ab(x^2+y^2)=?分解因式
2个回答
相关问题
-
分解因式:ab(x^2-y^2)-(a^2-b^2)(xy+1)-(a^2+b^2)(x+y)
-
分解因式a(x^2+2xy+y^2)-b(x^2-y^2)
-
6xy^2-9x^2y-y^3=?(2)(2a-b)^2+8ab=?分解因式
-
分解因式t^2-t-2,xy-x-y+1 x^2+6xy+8y^2 1-x^2+2xy-y^2 a^2-b^2+2ab-
-
分解因式(1)2a2b-4ab2+2ab(2)-2x2+8xy-8y2.
-
分解因式(1)5x^2y+10xy^2-15xy (2)3a^2b+6ab^2 (3)y(x-y)^2-(y-x)^3
-
分解因式:1.3x²-6√2xy-3y² 2.-3a²+4ab+2b²
-
x^2y-2xy^2+xy分解因式
-
分解因式:x2y-2xy+y=______.
-
-2xy-x2-y2分解因式